Study on etiology and clinical course of neonatal seizures and their outcome - Syed, Abdul Mohid; Reddy, Y. Shasidhar; Belavadi, Gangadhar B. (International Journal of Contemporary Pediatrics, 2019)
Background: The aim was to explore etiology, clinical course of neonatal seizure sand their and outcome in Narayana Medical College Hospital, Nellore, Andhra Pradesh, India. Methods: Retrospective study of 65 neonates from 1 month to 1 year diagnosed with epilepsy between November 2016 to August 2018. Results: Most common type of seizures seen are subtle (40%), followed by multifocalclonic (20%), tonic (21%), focal clonic (9.2%), clonic (7.7%) and myoclonic (1.6%). Most common cause of neonatal seizures was HIE (41.5%), followed by hypoglycemia (13.8%), intracranial bleed (10.8%), septicemia (10.8%), hypocalcemia (7.7%). The morality percentage is high (18.2%) when seizures occurred before 12 hours, when seizures occurred between 24-48 hrs it is 14.3%, and mortality was least when seizures occurred between 2-6 days (12.5%). Seizures are common in stage IIHIE (81.5%) compared to Stage I &Stage III. Seizures with adverse outcome are generalized myoclonic and focal clonic seizures. Focal clonic and focal tonic seizures are most often associated with focal injury. Generalized tonic seizures, motor automatism and some myoclonic seizures are associated with diffuse brain injury. Prolonged seizure activity, seizures lasting for many days, repetitive seizures, and the need for multiple anticonvulsants to control seizure activity are associated with an increased mortality. Conclusions: Authors conclude that prompt recognition, evaluation and treatment of these neonatal events are important in improving the survival of neonates with seizures.